How much reasonableness is there in the standard of a reasonable man? A few remarks regarding a reasonable man in Polish criminal law - Tarapata, Szymon (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
In this article the author presents how the figure standard of a reasonable man model citizen is used in Polish criminal law. It was shown that this standard is helpful mainly to determine the scope of unlawfulness adequate in a given situation limits of the conduct norm. The article also presents what factors are important in the process of applying a reasonable man standard.
Keywords: akcja; pominięcie; rozsądny człowiek; przypisanie konsekwencji; związek przyczynowy; przewidywalność